Coronavirus disease 2019 in a patient with pulmonary fibrosis and emphysema: An autopsy report - Risa Kudo; Takeshi Kawaguchi; Masatoshi Kimura; Yuuki Rikitake; Chihiro Iwao; Mao Rikitake; Kosho Iwao; Ayako Aizawa; Yumi Kariya; Motohiro Matsuda; Shunichi Miyauchi; Ichiro Takajo; et al. (Heliyon, 2023)
Various diseases (e.g., hypertension and diabetes) are risk factors for the exacerbation of coronavirus 2019 (COVID-19). Patients with chronic obstructive pulmonary disease (COPD) and interstitial lung disease (ILD) tend to develop severe COVID-19. Patients with severe COVID-19 present with acute respiratory distress syndrome (ARDS), and many COVID-19-related ARDS survivors eventually develop fibrosis. However, the appropriate management of patients with COVID-19 and ILD and post-COVID-19 ILD remains unclear. Thus, a better understanding of the pathology that exacerbates COVID-19 in patients with ILD is needed. We report the autopsy results of a patient with COVID-19 and combined pulmonary fibrosis and emphysema, whose lung organization and fibrosis progressed after the acute phase of infection. Histopathological findings suggest that fatal pulmonary fibrosis persists after the negative conversion of SARS-CoV-2. Elucidating the cause of death by autopsy may help determine therapeutic strategies in patients with COVID-19 and ILD. Vaccination and early administration of anti-inflammatory drugs or antifibrotic agents may be crucial for preventing disease progression and fatal lung fibrosis. This report aims to clarify the histopathological features of COVID-19 in patients with ILD via autopsy and discuss treatment strategies.